The prevalent anxiety disorders among elementary students in Bandung, Indonesia - Susanti Niman; Deo Kumala Dewa; Maria Yunita Indriarini (SAGE Publishing, 2021)
Background: Anxiety constitutes one of the most prevalent childhood mental health problems. It affects social functions, academic functions and increases the risk of mental health problems at the next stage of development among elementary school children. Besides, psychopathologic disorders in teenagers appear in form of emotional symptoms. Early anxiety screening is important for elementary students as anxiety disorders incur huge financial treatment costs, meanwhile, related data are needed to provide early and adequate interventions. This study is expected to be the basis for developing mental health programs at the elementary school level. Furthermore, aims to identify types of anxiety disorders among grade 4 and 5 students at the elementary level. Design and Methods: The study was conducted using a quantitative method with a descriptive design. Meanwhile, the Screen for Child Anxiety Related Disorders (SCARED) model consisting of 41 questions was used, while the instrument's Reliability and Validity was 0.81 and 0.67 respectively. A total of 135 students from the private elementary schools participated in this study. Results: Among the 135 elementary students aged 10 to 11, 48.9% were males while 51.1% were females, 79.3% had anxiety consisting of generalized anxiety 40%, panic disorder 48.1%, separation anxiety 40%, social anxiety 65.9%, while 28.9% experienced school avoidance. Conclusions: Based on the results, health workers, teachers and parents need to work together to manage anxiety in elementary students. In addition, nurses as health workers at community primary health need to work together with counselling and guidance teachers to provide preventive and promotive interventions through the school's mental health services.